2015
DOI: 10.1111/ijfs.12740
|View full text |Cite
|
Sign up to set email alerts
|

Drying characteristics and thermal degradation kinetics of hardness, anthocyanin content and colour in purple‐ and red‐fleshed potato (Solanum tuberosum L.) during hot air drying

Abstract: Summary Purple‐fleshed potatoes (PFP) and red‐fleshed potatoes (RFP) were dried using hot air. The hardness, anthocyanin content and colour in PFP and RFP during drying were evaluated at 60, 70 and 80 °C. The hardness was characterised by a softening stage in the early drying period, followed by a hardening stage. The times to reach at the transition were 420, 300 and 240 min at 60, 70 and 80 °C, respectively, for PFP, and 480, 360 and 240 min for RFP. However, the moisture content of both PFP and RFP at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Kim and others () have proved that baking at a high temperature (200 °C) only slightly reduced the total anthocyanin in purple potato (Kim and others ). Antioxidant levels in purple‐fleshed potato were 2 to 3 times higher than those of general white‐fleshed and yellow‐fleshed potatoes (Moon and others ). The HPLC analysis of individual anthocyanins in purple potato fried chips showed that petunidin derivates lost 40% to 62% and malvidin derivatives lost 15% to 49% (Kita and others ).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Kim and others () have proved that baking at a high temperature (200 °C) only slightly reduced the total anthocyanin in purple potato (Kim and others ). Antioxidant levels in purple‐fleshed potato were 2 to 3 times higher than those of general white‐fleshed and yellow‐fleshed potatoes (Moon and others ). The HPLC analysis of individual anthocyanins in purple potato fried chips showed that petunidin derivates lost 40% to 62% and malvidin derivatives lost 15% to 49% (Kita and others ).…”
Section: Resultsmentioning
confidence: 85%
“…We hypothesized that during the frying process of purple potato, remaining anthocyanins might react with precursors and thus block the formation of furan. Otherwise, the degradation of anthocyanins (Moon and others ) might have a bond with furan formation in purple potato in the frying process. Therefore, furan concentration decreased in fried purple potato slices compared to that of white potato slices and sweet potato slices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive microbial population in fresh-cut produce is another problem in fresh-cut industry [32,33]. UV-C is an environmental-friendly strategy for extending the shelf life of fresh-cut produce and has proved to be effective in reducing bacterial count but not damage other quality attributes [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…; Moon et al . ). Additionally, anthocyanin‐enriched resources have usually been considered to increase the quality of food (Einbond et al .…”
Section: Introductionmentioning
confidence: 97%